Effects of medial and lateral wedged orthoses on knee and ankle joint loading in female runners - Sinclair, Jonathan (Array, 2019)
The aim of the current investigation was to examine the effects of orthoses with a 5° medial and lateral wedge on knee and ankle joint kinetics in female runners. Twelve healthy female runners ran at 3.5 m/s over a force platform in three conditions (medial, lateral and no-orthotic). Lower extremity kinematics were measured using an 8-camera motion capture system, which allowed knee and ankle loading to be explored using a musculoskeletal modelling approach. The peak Achilles tendon force was significantly larger in the no-orthotic condition (5.34 BW) compared to the lateral orthosis (5.03 BW). The peak patellofemoral stress was significantly larger in the medial orthosis (7.32 MPa) compared to the no-orthotic (7.02 MPa) condition. Finally, the peak knee adduction moment was significantly larger in the medial condition (1.14 Nm/kg) compared to the lateral (0.99 Nm/kg) orthosis. The findings from the current investigation indicate that lateral orthoses may be effective in attenuating risk of medial tibiofemoral osteoarthritis and Achilles tendinopathy, but medial wedge orthoses may increase the risk of patellofemoral pain in female runners.